2021
DOI: 10.2147/dddt.s304162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dexmedetomidine on Postoperative Sleep Quality: A Systematic Review

Abstract: In this article, we conduct a systematic review of the literature to explore the specific role of dexmedetomidine (DEX) on postoperative sleep and its associated mechanisms at present. The electronic database Embase, MEDLINE/PubMed, the Cochrane Library, Web of Science, and Google Scholar were searched. The restriction terms included "dexmedetomidine", "sleep" and "surgery". The inclusion criteria were as following: 1) patients 18 years old or older; 2) DEX used in the perioperative period not just for critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 41 publications
3
21
3
1
Order By: Relevance
“…Dexmedetomidine is widely used as a sedative. In 2021, Huang et al published a systematic review showing that dexmedetomidine had advantages in improving postoperative sleep quality, 34 which was consistent with our results that dexmedetomidine improved the RCSQ scores in elderly patients undergoing oral and maxillofacial surgery. Sleep deprivation was reported to be closely related to delirium, 35 however, in this study, dexmedetomidine improved sleep quality but did not improve delirium symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…Dexmedetomidine is widely used as a sedative. In 2021, Huang et al published a systematic review showing that dexmedetomidine had advantages in improving postoperative sleep quality, 34 which was consistent with our results that dexmedetomidine improved the RCSQ scores in elderly patients undergoing oral and maxillofacial surgery. Sleep deprivation was reported to be closely related to delirium, 35 however, in this study, dexmedetomidine improved sleep quality but did not improve delirium symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…Dexmedetomidine acts on the α2 adrenoceptor agonist in the nucleus locus coeruleus, reduces the release of norepinephrine, simulates natural sleep, and produces sedative, hypnotic, and anxiolytic effects ( 28 , 29 ). In the present study, we found that dexmedetomidine combined with butorphanol can improve the sedative effects (according to the Ramsay score) in continuous analgesia after a cesarean section, and the analgesic and sedative effects of dexmedetomidine in the high-dose group are better than those in the low-dose group, which is consistent with the findings of Zhang et al ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“… 102 A recent systematic review showed that dexmedetomidine has advantages in improving patients’ postoperative sleep quality. 103 Other studies have also assessed the feasibility of patient-controlled sleep with dexmedetomidine in treating chronic intractable insomnia. Patient-controlled analgesia (PCA) is an “on-demand” system that allows patients to self-administer intravenous medications in small bolus doses.…”
Section: Clinical Effectsmentioning
confidence: 99%